Identification of Hub Genes Associated With Hepatocellular Carcinoma Using Robust Rank Aggregation Combined With Weighted Gene Co-expression Network Analysis - Song, Hao; Ding, Na; Li, Shang; Liao, Jianlong; Xie, Aimin; Yu, Youtao; Zhang, Chunlong; Ni, Caifang (Frontiers in Genetics, 2020)
Abstract Background: Bioinformatics provides a valuable tool to explore the molecular mechanisms underlying pathogenesis of hepatocellular carcinoma (HCC). To improve prognosis of patients, identification of robust biomarkers associated with the pathogenic pathways of HCC remains an urgent research priority. Methods: We employed the robust rank aggregation (RRA) method to integrate nine qualified HCC datasets from the Gene Expression Omnibus (GEO). A robust set of differentially expressed genes (DEG) between tumor and normal tissue samples was screened. Weighted gene co-expression network analysis (WGCNA) was applied to cluster DEGs and the key modules related to clinical traits identified. Based on network topology analysis, novel risk genes derived from key modules were mined and biological verification performed. The potential functions of these risk genes were further explored with the aid of miRNA-mRNA regulatory networks. Finally, the prognostic ability of these genes was assessed by constructing a clinical prediction model. Results: Two key modules showed significant association with clinical traits. In combination with protein-protein interaction (PPI) analysis, 29 hub genes were identified. Among these genes, 19 from one module showed a pattern of upregulation in HCC and were associated with tumor node metastasis (TNM) stage, and 10 from the other module displayed the opposite trend. Survival analyses indicated that all these genes were significantly related to patient prognosis. Based on the miRNA-mRNA regulatory network, 29 genes strongly linked to tumor activity were identified. Notably, five of the novel risk genes, ABAT, DAO, PCK2, SLC27A2, and HAO1, have rarely been reported in previous studies. Gene set enrichment analysis (GSEA) for each gene revealed regulatory roles in proliferation and prognosis of HCC. Least absolute shrinkage and selection operator (LASSO) regression analysis further validated DAO, PCK2 and HAO1 as prognostic factors in an external HCC dataset. Conclusion: Analysis of multiple datasets combined with global network information presents a successful approach to uncover the complex biological mechanisms of HCC. More importantly, this novel integrated strategy facilitates identification of risk hub genes as candidate biomarkers for HCC, which could effectively guide clinical treatments.